PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN PENGALAMAN KERJA GURU TERHADAP KINERJA GURU DENGAN EFIKASI DIRI SEBAGAI VARIABEL INTERVENING - Ika Yuliandari; Widiyanto; Agus Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is one of the important sectors that must be considered by the government of developing countries such as Indonesia. The progress of education will not be separated from the role of teachers as the spearhead of education. However, teacher performance can be influenced by several factors, including the principal's leadership, the environment in which teachers work, and their work experience. In addition, the self-efficacy of teachers can also have an influence either directly or as a mediation of other factors. This study aims to examine the effect of leadership, work environment, and work experience on teacher performance with self-efficacy as an intervening variable. This research is a quantitative study with a correlational design. The sample used in this study amounted to 292 respondents selected by purposive sampling technique from the population of public junior high school teachers in Temanggung Regency. Data were collected through questionnaires and processed using the Structural Equation Modeling (SEM) method with the WarpPLS analysis tool. This study concluded that leadership, work environment, and self-efficacy directly affect teacher performance, while work experience does not directly affect teacher performance. Leadership, work environment, and work experience affect self-efficacy. As for the indirect effect, self-efficacy does not mediate the effect of leadership, work environment, and work experience.